Clinical Presentation and Outcome of Management of Congenital Heart Diseases Associated with Down Syndrome in a Tertiary Care Hospital - Ferdous, Jannatul; Begum, Nurun Nahar Fatema; Rashid, Md Harun Or (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Treatment of children with Down syndrome having congenital heart defects has not been reported well in Bangladesh. This study has been carried out to inform practitioners about findings from cases in Combined Military Hospital, Dhaka. Methods: Three years retrospective observational study (clinical data, hospital course and follow-up) was carried out on 114 patients (49 males and 65 females, age range 1 month to 12 years) who underwent diagnostic and therapeutic work up in the pediatric cardiology department CMH Dhaka between January 2018 and December 2020. Results: Among 114 patients ,64 were (57%) were infants and 50 were older children (43%) , twenty-five had congestive cardiac failure and eighteen had hypothyroidism. The study showed that 33.3% were atrioventricular septal defect (AVSD), 28.1% were patent ductus arteriosus (PDA),8.75% were tetralogy of Fallot (TOF) ,5.25% were coartation of aorta (COA) ,3.5% were patent ductus arteriosus with coarctation of aorta 3.5%, double outlet right ventricle with pulmonary stenosis were 3.5%, ventricular septal defect were 7% whereas atrial septal defect along with ventricular septal defect were 5.3% ,atrial septal defect were 3.5%, transposition of great arteries with multiple ventricular septal defect were 1.8%.Forty (35%) patients using per cutaneous intervention,had 100% procedural success and no mortality .45 patients underwent surgery,few of them were not operated due to severe pulmonary hypertension. Conclusion: Congenital heart disease was more frequent in DS children,having worse prognosis.Children with DS required special attention due to increased risk of pulmonary hypertension. Delayed treatment was an important risk factor for poor prognosis.So early diagnosis is needed in order to provide optimal intervention and surgery ,before occurrence of irreversible PAH. J Bangladesh Coll Phys Surg 2023; 41: 7-14